The Naucoridae - Sites, Robert W; Bergsten, Johannes (PloS one, 2022)
The island nation of Madagascar was surveyed extensively through a series of expeditions to determine the fauna of Naucoridae. Previously, 17 species in four genera had been reported from the country. All taxa previously recorded from Madagascar were re-collected, with the exception of three species, Macrocoris flavicollis Signoret, Temnocoris starmuhlneri Poisson, and Tsingala nossibeanus (Bergroth). Macrocoris flavicollis is removed from the list of species occurring in Madagascar. Within Laccocorini (Laccocorinae), a new genus, Gonioathrix n.gen. is described; Temnocoris and Tsingala are revised; three new species are described in Temnocoris (T. leachi n.sp., T. montandoni n.sp., T. poissoni n.sp.) and four in Tsingala (T. angulata n.sp., T. latiforma n.sp., T. spatulata n.sp., T. trilobata n.sp.). Lectotypes are designated for Afronaucoris madagascariensis (Montandon), Tsingala humeralis (Signoret), and T. naucoroides (Montandon). In Macrocorinae, a new species of Macrocoris, M. namorona n.sp., from Ranomafana National Park is described. These taxonomic actions bring the total for the country to five genera and 25 species. Distributions, habitat associations, and a key to the species are presented.